Remobilization of century-old magmas during the 2018 basaltic caldera-forming eruption at Kīlauea Volcano (Hawai‘i) - Mourey, Adrien J. (2025)
The recent eruptions at Kīlauea Volcano (Hawai‘i) raised some fundamental questions on the longevity and the preservation of eruptible magma batches left over from previous eruptions. Fingerprinting magma batches at Kīlauea through time with bulk and glass compositions is challenging. Narrow compositional changes (e.g., Nb/Y ratio) in matrix glasses occur over time because of repeated magma mixing, and residence timescales of stored evolved magmas in the lower East Rift Zone are underconstrained. To evaluate the diversity in composition and the minimum residence timescales in Rift Zone magmas, we analyzed major and trace elements in plagioclase and matrix glasses from selected samples that erupted in the first weeks of the 2018 Kīlauea eruption. Plagioclase crystals in these samples represent mixed populations with a range in composition spanning An30-80, corresponding to rhyodacitic to basaltic compositions and temperatures from 950 to 1200 °C. Diffusion modeling of Mg in these plagioclase crystals indicate minimum crystal residence timescales that range from < 1 to ~ 480 years. The complex zoning patterns in plagioclase (and resorptions) together with the protracted storage timescales from diffusion modeling imply that magmas from the East Rift Zone accumulated various plagioclase populations recording magma mixing events that occurred a few years to a few centuries before the 2018 eruption. The diversity of the magma batches (observed with An-Mg compositions in plagioclase) erupted in a single eruption offers research pathways to potentially estimate the frequency, volume and eruptibility of these evolved magmas, thereby refining the risk in the region.